Long Length of Stay Associated with Geriatric Open Ankle Fractures - Alynna Xu Y Chua; Manu J Abraham; Yuet Peng Khor (Journal of Foot and Ankle Surgery (Asia Pacific))
Background: There is an increasing incidence of geriatric ankle fractures worldwide. We aim to review the management and outcomes of geriatric open ankle fractures at our institution. Materials and methods: A retrospective review of medical records of all patients above 60 years of age who had surgery for open ankle or distal tibia and fibula fractures between the years 2017 and 2021 was performed. Demographic data, ambulatory outcomes, comorbidities, surgical management, length of stay, complications, and radiographic data were recorded. A descriptive analysis of their management and outcomes was performed. Results: Around 12 of 99 patients above the age of 60 years had open ankle/distal tibia and fibula fractures. The mean age was 69.5 years (61–85 years), and seven were female patients (58%). Around 67% (n = 8) of patients had low-energy falls. The average follow-up was 8.6 months (2 weeks–32 months). Around 42% were Gustilo–Anderson grade 1, 33% grade 2, 8% grade 3A, and 17% grade 3B injuries. The mean length of stay for patients with open fractures was 13.5 days compared to 10.8 days for closed fractures. Patients spent a mean of 52.6 days (28–77 days) at the step-down facility. The 1-year mortality rate was 8%. Around 50% of patients returned to their previous ambulatory status. The rate of malunion and posttraumatic arthritis was 11% each. There were no cases of deep surgical site infection or amputation. Conclusion: Patients with open geriatric ankle fractures required a long length of stay at the institution, and only 50% returned to their previous ambulatory status.